2018
DOI: 10.1177/2167702618782194
|View full text |Cite
|
Sign up to set email alerts
|

The Personality Trait of Environmental Sensitivity Predicts Children’s Positive Response to School-Based Antibullying Intervention

Abstract: The personality trait of environmental sensitivity predicts children's positive response to school-based anti-bullying intervention. Clinical Psychological Science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 42 publications
9
104
0
2
Order By: Relevance
“…Specifically, girls scoring high on SPS showed a significant reduction in depression symptoms, which was evident at six and 12-month follow ups, whereas girls low in sensitivity did not show any significant change. These findings of heightened responsivity to positive experiences in individuals scoring high in SPS have recently been replicated in a large randomized control trial (N = 2,024) testing the efficacy of a schoolbased anti-bullying intervention (Nocentini et al, 2018). In line with expectations, the results of this study showed that the intervention significantly decreased victimization and bullying across the entire sample.…”
Section: Sps As a Marker Of Differential Susceptibilitysupporting
confidence: 80%
See 3 more Smart Citations
“…Specifically, girls scoring high on SPS showed a significant reduction in depression symptoms, which was evident at six and 12-month follow ups, whereas girls low in sensitivity did not show any significant change. These findings of heightened responsivity to positive experiences in individuals scoring high in SPS have recently been replicated in a large randomized control trial (N = 2,024) testing the efficacy of a schoolbased anti-bullying intervention (Nocentini et al, 2018). In line with expectations, the results of this study showed that the intervention significantly decreased victimization and bullying across the entire sample.…”
Section: Sps As a Marker Of Differential Susceptibilitysupporting
confidence: 80%
“…The analysis of the factorial structure of the scale indicated that the HSC scale has adequate internal consistency and good psychometric properties across independent samples (Pluess et al, 2017;Weyn et al, under review). Its criterion validity has been confirmed by showing that children scoring high on this scale are more sensitive and responsive to the positive influence of psychological interventions (Nocentini, Menesini, & Pluess, 2018;Pluess & Boniwell, 2015), as well as to both positive and negative parenting quality (Slagt et al, 2017).…”
Section: Sps Scales: the Highly Sensitive Person (Hsp) And Highly Senmentioning
confidence: 90%
See 2 more Smart Citations
“…More recently, a range of new measures have been developed to assess sensitivity in children, including the 12-item Highly Sensitive Child (HSC) scale (Pluess et al, 2018) and the Highly Sensitive Child-Rating System (HSC-RS) (Lionetti, Aron, Aron, Klein, & Pluess, 2019), an observer-rated measure of sensitivity in young children. According to longitudinal and experimental studies, children that score high on these measures have been found to be more affected by their experiences such as school-based psychological programmes (Nocentini, Menesini, & Pluess, 2018;Pluess & Boniwell, 2015) and parenting quality (Lionetti, Aron, et al, 2019;Slagt, Dubas, van Aken, Ellis, & Dekovic, 2018).…”
Section: Empirical Evidencementioning
confidence: 99%